The effects of nebulizer hygiene training on the practices of cystic fibrosis patients and caregivers - ERGENEKON, ALMALA PINAR; KARADAĞ, BÜLENT TANER; YILMAZ YEĞİT, CANSU; ERDEM ERALP, ELA; GÖKDEMİR, YASEMİN (WILEY, 2021)
Background Nebulizers can be contaminated with microorganisms and may be a source of infection in the lower airways in patients with cystic fibrosis (CF). Objective Primary aim of this study was to determine the level of knowledge regarding nebulizer hygiene and adherence to CF foundation infection prevention and control (IPC) measures of CF patients in our center. We also evaluated the effect of a standardized training program on nebulizer cleaning and disinfection practises with pre and posttest. Methods Caregivers of 173 CF patients followed at Marmara University CF Center filled a questionnaire (pretest) regarding nebulizer hygiene and received didactic education including pictures and videos based on the cystic fibrosis foundation (CFF) IPC guidelines, patients were also provided educational materials. Posttest was performed 1-3 months after the education session. Results Following standardized training, usage of appropriate methods according to CFF IPC guidelines improved significantly. Frequency of nebulizer cleaning after each use increased from 58.4% to 78% (p < .01) and disinfection frequency after each/daily usage increased from 33.6% to 75.7% (p < .01). Additionally, methods of cleaning and storage of the nebulizer, also improved significantly (p < .01, p < .01). Conclusion Education was highly effective to increase the rate of proper practices for nebulizer hygiene. The necessity of cleaning, disinfection, careful drying, correct storage of the nebulizer parts, and changing the nebulizer equipment within recommended time should be emphasized to CF families regularly.
Keywords: cystic fibrosis; nebulizer hygiene; standardized training